Treatment of myofascial trigger points in patients with chronic shoulder pain: a randomized, controlled trial - Stegenga Boudewijn (BMC Medicine, 2011)
Abstract Background Shoulder pain is a common musculoskeletal problem that is often chronic or recurrent. Myofascial trigger points (MTrPs) cause shoulder pain and are prevalent in patients with shoulder pain. However, few studies have focused on MTrP therapy. The aim of this study was to assess the effectiveness of multimodal treatment of MTrPs in patients with chronic shoulder pain. Methods A single-assessor, blinded, randomized, controlled trial was conducted. The intervention group received comprehensive treatment once weekly consisting of manual compression of the MTrPs, manual stretching of the muscles and intermittent cold application with stretching. Patients were instructed to perform muscle-stretching and relaxation exercises at home and received ergonomic recommendations and advice to assume and maintain good posture. The control group remained on the waiting list for 3 months. The Disabilities of Arm, Shoulder and Hand (DASH) questionnaire score (primary outcome), Visual Analogue Scale for Pain (VAS-P), Global Perceived Effect (GPE) scale and the number of muscles with MTrPs were assessed at 6 and 12 weeks in the intervention group and compared with those of a control group. Results Compared with the control group, the intervention group showed significant improvement (P < 0.05) on the DASH after 12 weeks (mean difference, 7.7; 95% confidence interval (95% CI), 1.2 to 14.2), on the VAS-P1 for current pain (mean difference, 13.8; 95% CI, 2.6 to 25.0), on the VAS-P2 for pain in the past 7 days (mean difference, 10.2; 95% CI, 0.7 to 19.7) and VAS-P3 most severe pain in the past 7 days (mean difference, 13.8; 95% CI, 0.8 to 28.4). After 12 weeks, 55% of the patients in the intervention group reported improvement (from slightly improved to completely recovered) versus 14% in the control group. The mean number of muscles with active MTrPs decreased in the intervention group compared with the control group (mean difference, 2.7; 95% CI, 1.2 to 4.2). Conclusions The results of this study show that 12-week comprehensive treatment of MTrPs in shoulder muscles reduces the number of muscles with active MTrPs and is effective in reducing symptoms and improving shoulder function in patients with chronic shoulder pain. Trial registration number ISRCTN: ISRCTN75722066